INDUCTION OF LIGNINOLYTIC ENZYMES OF THE FUNGUS SCHIZOPHYLLUM COMMUNE (Eurasian Journal of Ecology, 2024)
The study focuses on the induction of ligninolytic enzymes that can replace alkaline solutions used to separate lignin from cellulose. Schizophyllum commune pure rot fungus culture was identified as a producer and wheat was used as a substrate in the solid phase fermentation process. The experiment was carried out in three parallels: a control sample without a biological object, a sample with the S. commune fungus, a sample with the S. commune fungus and an inductor in the form of CuSO4 at 30 ± 2°C for 30 days, the moisture content of the nutrient substrate was 70%. Every 10 days, a sample was taken from each sample for quantitative analysis of lignin, which was carried out according to the Klarson method modified by Komarovsky. The initial amount of lignin in the control sample was 20.16% on the 30th day, the content of lignin with the S.commune fungus without the inductor was 10.15%, while in the sample with the glaucoma and the introduction of the CuSO4 inductor, a decrease to 8.6% was observed, which much more efficient. The high activity of ligninolytic enzymes produced by the fungus during induction proves the possibility of partial or complete replacement of chemical reagents with natural enzymes, which will significantly reduce the amount of toxic emissions into the environment pulp and paper manufacturing.Key words: S.commune, ligninases, manganese peroxidase, lignin peroxidase, inductor, copper, ecology, toxic emissions